PENGARUH STRUKTUR MODAL, KINERJA KEUANGAN PERUSAHAAN DAN PEMBAGIAN DIVIDEN TERHADAP NILAI PERUSAHAAN PADA SUB-SEKTOR PERTAMBANGAN BATU BARA YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2019-2023: PENGARUH STRUKTUR MODAL, KINERJA KEUANGAN PERUSAHAAN DAN PEMBAGIAN DIVIDEN TERHADAP NILAI PERUSAHAAN PADA SUB-SEKTOR PERTAMBANGAN BATU BARA YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2019-2023 - Sri wahyuti; Rudy Syafariansyah; nur nabilla; agus riyanto (Economic Faculty, University of Widya Gama Mahakam Samarinda, 2025)
This study aims to analyze and test the effect of capital structure, company financial performance, and dividend distribution on company value in the coal mining sub-sector listed on the Indonesia Stock Exchange for the period 2019-2023. The research method used is quantitative with secondary data obtained from the official website of the Indonesia Stock Exchange (www.idx.co.id). The independent variables in this study include capital structure as measured by Debt to Equity Ratio (DER), financial performance as measured by Return on Assets (ROA), and dividend distribution as measured by Dividend Payout Ratio (DPR), while the dependent variable is company value as measured by Price to Book Value (PBV). The results showed that capital structure did not have a significant effect on company value with a t-count value of -1.563 and a significance of 0.128> 0.05. Company financial performance also did not have a significant effect on company value with a t-count value of -1.429 and a significance of 0.163> 0.05. Likewise, dividend distribution does not have a significant effect on company value with a t-count value of -0.517 and a significance of 0.609> 0.05. The results of the simultaneous test also show that the three independent variables together do not have a significant effect on company value with an F-count value of 2.225 <F-table 3.16 and a significance of 0.105> 0.05. The coefficient of determination value of 0.177 indicates that only 17.7% of the variation in company value can be explained by the three independent variables, while the remaining 82.3% is explained by other factors outside the research model. This study highlights the importance of exploring other determinant factors that may be more relevant in the formation of company value in the coal mining industry